El Periodo Formativo en Ayacucho: balances y perspectivas - Ochatoma, José (Pontificia Universidad Católica del Perú. Fondo Editorial, 1998)
Este trabajo presenta una síntesis de los estudios acerca del Periodo Formativo en Ayacucho con una historia de las investigaciones (1959 al presente), una discusión crítica de los principales sitios y una interpretación general del desarrollo socioeconómico. Se desprende que aún subsisten muchas lagunas y algunos de los sitios con arquitectura monumental ya fueron destruidos o no están disponibles para estudios futuros.

The Formative Period in Ayacucho: Balance and PerspectivesThe present paper presents the synthesis of the state of knowledge of Ayacucho Formative starting with the history of investigations (1959 to present), a critical assessment of the principal sites and a general interpretation of its socioeconomic development. It reveals still existing problems due to insufficient knowledge and the fact that most of the major sites with monumental architecture have been destroyed or are not available for study any longer.
Keywords: Arqueología; Periodo Formativo; Sierra Central; Ayacucho; Evidencias Arqueológicas; Archaeology; Formative Period; Central Highlands; Ayacucho; Archaeological Evidences; https://purl.org/pe-repo/ocde/ford#6.01.02